Linking the formation and fate of exo-Kuiper belts within Solar system analogues - Veras, Dimitri; Stock, Katja; Flammini Dotti, Francesco; Cai, Maxwell X.; Mustill, Alexander J.; Shannon, Andrew; McDonald, Catriona H.; Portegies Zwart, Simon; Kouwenhoven, M. B. N.; Spurzem, Rainer (Monthly notices of the Royal Astronomical Society, 2020)
ABSTRACT. Escalating observations of exo-minor planets and their destroyed remnants both passing through the Solar system and within white dwarf planetary syst
In original form 2019 November 28
Gesehen am 22.10.2020